Real-time automatic target detection and tracking using visual feedback - Khan, A. (IEEE Computer Society, 2014)
This paper presents the use of visual feedback for feedback control system. There may be situations where an appropriate sensor or measuring device may not always be available/applicable or useful. Intrusion movement is one example where we cannot place a sensor on the object. This paper employs the visual feedback control to detect and track a moving object using 2-degree-of-freedom robotic system. The proposed system is capable of real-time detection and tracking of a known object moving in a given scenario. Experimental results show reasonable performance, promising to be used for unknown object in unknown environment. Â© 2014 IEEE.